Bottom-up factors of attention during the tourist experience: an empirical study. Issue 24 (16th December 2020) - Campos, Ana Cláudia; Pinto, Patrícia; Scott, Noel
ABSTRACT: Tourism, by definition, involves travel outside one's usual environment. This means that a tourist's attention cannot rely only on previously experienced known symbols and markers and instead derives meaning from paying attention to their surroundings. In this context, management of a visitor's attention processes is a key issue in the design of memorable tourist experiences and business success. Psychological research highlights two types of attention processes: bottom-up and top-down. This research is the first to identify factors influencing bottom-up attention during on-site experience and to examine the moderating impact of top-down factors of attention. The empirical research used questionnaires obtained from tourists participating in two animal-based experiences at a theme park. The results show that of the bottom-up factors analyzed, only two influenced attention, Rarity and Environment stimulation . Concerning the moderating influence of top-down factors, the research found that Interpersonal interaction and Task performance/Goal achievement affect the way external factors impact on attention, and that the intensity of this relation varies according to the relevance of this moderation.